Strategy for Increasing Rural and Urban Land and Building Tax Revenue (PBB-P2) at The Regional Revenue Agency of West Kutai Regency - Ria Pitriana; Yonathan Palinggi; Musmuliadi Musmuliadi (Publikasi Indonesia, 2022)
Local governments are expected to increase PAD to reduce dependence on financing from the center, so as to increase regional autonomy and discretion (local discretion). This study aims to determine the strategy for increasing revenue from the Land and Building Tax in Rural and Urban (PBB-P2) in West Kutai Regency, the factors that hinder the achievement of the strategy for increasing PBB-P2 revenues and the factors that can support the achievement of the strategy for increasing PBB-P2 revenues. at the Regional Revenue Service (Bapenda) of West Kutai Regency. This type of research is descriptive qualitative research. The type of data used in this study is primary data obtained from interviews with research informants and secondary data in the form of reports and official documents. The research instrument is the researcher himself who in its implementation uses tools in the form of interview guidelines and observation guidelines. The data collection technique used is in the form of interviews, observation and documentation, while the data analysis technique used is in the form of descriptive analysis, namely by interpreting the data, facts, and information obtained. The results showed that the strategy adopted by the Bapenda of West Kutai Regency in increasing PBB-P2 revenues included forming a tax collection officer in the sub-district, socializing SPPT to the community through banners, especially when it was nearing maturity, issuing a Tax Billing Letter (STP) and conducting doorsteps. door to door as well as holding PBB payment week. Factors that hinder the achievement of the strategy to increase PBB-P2 revenue in West Kutai Regency are, among others, due to technological factors, limited facilities and infrastructure, inadequate human resources, and budget constraints, while factors that can support include the commitment of resources. human resources, supportive political and social conditions and a sufficient number of employees.